(untitled) (Nativa, 2018)
No intuito de elevar as taxas de sobrevivência durante a etapa de aclimatização e posterior plantio a campo, avaliou-se o enraizamento in vitro de bananeira cv. Pacovan, em diferentes concentrações de sais MS e de sacarose. Utilizou-se DIC, esquema fatorial (6x2x3), com seis meios de cultura [sendo três concentrações de nutrientes do meio MS (100%; 50% de macronutrientes; e 50% dos sais macro e micronutrientes), e duas concentrações de sacarose (1,5/3,0%)], dois fotoperíodos (12/16 h) e três tempos de cultivo (21, 28 ou 35 dias) e seis repetições/tratamento. Analisaram-se: altura da planta, número de folhas/planta, massas frescas e secas das partes aérea e radicular. Para altura da planta, massa fresca da parte aérea e radicular, o meio MS 50% dos sais + sacarose (1,5%) com fotoperíodo de 16 h e tempo de cultivo de 35 dias foi satisfatório. Para massa seca da parte aérea foi MS 50% de sais + sacarose (3%), e para massa seca da parte radicular, MS 100% + sacarose (3%) (em 12hs/28 dias e 16hs/21 dias). Para o alongamento/enraizamento in vitro da bananeira cv. Pacovan sugere-se MS 50% de sais (macro e micronutrientes), redução ou manutenção de sacarose (1,5 ou 3%) em 16h/35 dias de cultivo. Palavra-chave: Musa spp., propagação in vitro, sistema radicular. CHANGES IN CULTURE MEDIUM, PHOTOPERIOD AND TIME OF CULTIVATION AFFECT THE IN VITRO ELONGATION AND ROOTING OF BANANA CV. PACOVAN ABSTRACT: In order to achieve high rates of survival during the acclimatization and later planting in the field, was evaluated the in vitro of banana cv. Pacovan plants under different concentrations of sucrose and MS basal salt mixture. The experiment was assembled in a DIC, in 6x2x3, six different culture media [three different MS salt mixture concentrations (100%; 50% of macronutrients; and 50% of macro/micronutrients) and two sucrose concentrations (1.5/3%)], two photoperiods (12/16 hours) and three cultivation times (21, 28 or 35 days). Each treatment was composed by 6 replicates. Plant height, number of leaves/plant, fresh and dry weight of roots and shoots, were analyzed. Satisfactory results for plant height and shoot and root fresh biomass were observed in MS with macro/micronutrients (50%) + sucrose (3%), 16 hours/35 days. The highest values of shoot dry weight were observed in MS with macro/micronutrients (50%) + sucrose (3%); the highest root dry weight was achieved with MS 100% + sucrose (3%) (12hs/28 and 16hs/21 days). The suggested medium for the in vitro elongation and rooting stage of banana cv. Pacovan is the MS with 50% of salts (macro and micronutrients), reduction or maintenance of sucrose (1.5 or 3%) in 16h/35 days of cultivation. Keywords: Musa spp., in vitro propagation, root system.